Construction of a Web Game for the Teaching-Learning Process of Electronics during the COVID-19 Pandemic - Ricardo-Adán Salas-Rueda, Clara Alvarado-Zamorano, Jesús Ramírez-Ortega (Educational Process: International Journal)
Background/purpose – During the COVID-19 pandemic, teachers were required to update school activities using various technological tools. The aim of this mixed research was the construction and usage analysis of the Digital Game for the teaching-learning process on Electronics (DGE) version 3.0 in the Combinational Circuits unit through data science.